Sifat Mekanik dan Struktur Mikro Logam Paduan Mg-1.6Gd Sebagai Biomaterial yang Larut di dalam Tubuh - Oknovia Susanti; Ilhamdi Ilhamdi; Muhammad Ivan Herdian (Metal: Jurnal Sistem Mekanik dan Termal)
Recently, the uses of magnesium alloys as implant materials have been potentially applications as biocompatible materials. In this case, the Mg alloys were being concerned because of their mechanical properties that were nearly similar to bones. The addition of Gd in magnesium was in order to control the degradation of magnesium. It is well known that the mechanical properties of Mg-1.6Gd alloys is improved by the small addition. The hardness of the alloys is obtained by the Vickers test with a different position on the samples. The lowest hardness value is 39 HVN, and the highest hardness value is 50 HVN, with the average one is 43.85HVN. Meanwhile, the pure magnesium had 30 HVN. Thus, it could be said that the addition of gadolinium elements could increase the hardness value. Then the tensile test is used a UTM (Universal Testing Machine). The test is used three same untreated samples. From the test are got the ultimate tensile strength of 97-117 MPa, but the ultimate strength of the magnesium is 60 MPa. Microscope optically is used to investigate the microstructure. The grain area is calculated by using the ImageJ program. The result showed that the lowest one is 16  and the highest one is 97.